Tendon Vasculature in Health and Disease - Tempfer, Herbert; Traweger, Andreas (Frontiers in Physiology, 2015)
Tendons represent a bradytrophic tissue which is poorly vascularized and, compared to bone or skin, heal poorly. Usually, a vascularized connective scar tissue with inferior functional properties forms at the injury site. Whether the increased vascularization is the root cause of tissue impairments such as loss of collagen fibre orientation, ectopic formation of bone, fat or cartilage, or is a consequence of these pathological changes remains unclear. This review provides an overview of the role of tendon vasculature in healthy and chronically diseased tendon tissue as well as its relevance for tendon repair. Further, the nature and the role of perivascular tendon stem/progenitor cells residing in the vascular niche will be discussed and compared to multipotent stromal cells in other tissues.